Predictive factors of major deviation (>20 mm) between lesion sizes measured by magnetic resonance imaging and histology for invasive lobular breast cancer. (August 2020) - Gest, Roxane; Cayet, Sophie; Arbion, Flavie; Vildé, Anne; Body, Gilles; Ouldamer, Lobna
Abstract: Objective: To identify factors predictive of high discordance (>20 mm) between lesion sizes measured by magnetic resonance imaging (MRI) and histology for invasive lobular breast cancer. Materials and methods: Data for all women with invasive lobular breast cancer (pure or associated with a component of invasive ductal carcinoma) between 1st January 2007 and 31st December 2016 were included in this study. Logistic regression analysis was performed to determine factors predictive of high discordance (underestimation/overestimation by >20 mm) between tumour sizes measured by MRI and histology for invasive lobular breast cancer. Results: For overestimation, significant factors on univariate analysis were: menopausal status [odds ratio (OR) 0.27, 95 % confidence interval (CI) 0.10–0.71]; p  = 0.01], hormone receptor (HR) status (HR negative, OR 1.64, 95 % CI 0.27–9.89; HR positive, OR 0.64, 95 % CI 0.21–1.88; p  = 0.09) and neoadjuvant chemotherapy (OR 10.33, 95 % CI 3.58–29.8; p  < 0.001). On multivariate analysis, menopausal status and neoadjuvant chemotherapy were found to be independent predictive factors of overestimation. For underestimation, significant factors on univariate analysis were: histological size (OR 1.05, 95 % CI 1.02–1.08; p  < 0.0001) and the presence of an in-situ component (OR 4.66, 95 % CI 1.01–21.5; p  = 0.02). These two factors were independent predictive factors of underestimation. Conclusion: Independent predictive factors of overestimation/underestimation (threshold 20 mm) of tumour sizes measured by MRI compared with histology for invasive lobular breast cancer were identified.